Uji Homogenitas dengan Sebaran Khi-Kuadrat dalam Evaluasi Suatu Sistem - Sungkawa, Iwa (Bina Nusantara University, 2011)
This paper discusses the application of khi-square distribution in homogeneity of variance test on the control of a system used in a process considered normally spread with a mean of and a variance (degree of homogeneity) of . It is necessary to test the hypothesis statistically Ho: with the average μo value is unknown, and the statistic used is Khi-square distribution. On this occasion, an evaluation is executed upon a